4. Principles of Art from Antiquity to Contemporary Pedagogy in the Context of Methodology of Art Education - Olimpiada Arbuz-Spatari (Sciendo, 2016)
The methodologies of Art Education is a system of educational documents - principles, rules, methods, procedures, forms - designed determinative - reflective thinking from teleology, content, communication arts / cultural / scientific, reception and receiver topic communicating, and are subject oriented educated / creator student under the laws of education, communication and artistic principles.